1989
DOI: 10.1128/iai.57.4.1018-1024.1989
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rat model for respiratory infection with Bordetella pertussis

Abstract: Considerable effort directed toward designing a safe and effective vaccine for Bordetella pertussis in which the cellular and/or acellular antigens necessary to confer immunity are known has been hampered by lack of information on the pathogenesis of the natural infection. The study presented here describes an animal model of lung infection by B. pertussis encased in agar beads in adult (200- to 220-g) male Sprague-Dawley rats. At 3 and 7 days after inoculation with phase I B. pertussis, organisms could be rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
31
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 8 publications
4
31
0
Order By: Relevance
“…The model has for example been used to investigate the effect of chronic P aeruginosa lung infection on the pulmonary circulation (1 6) and the effect of ibuprofen therapy on chronic P aeruginosa lung infection (36). Others have used Bordetella pertussis (58) and Haemophilus infruenzae (39,50) in similar studies of chronic pneumonia.…”
Section: Johansen Ct Almentioning
confidence: 99%
“…The model has for example been used to investigate the effect of chronic P aeruginosa lung infection on the pulmonary circulation (1 6) and the effect of ibuprofen therapy on chronic P aeruginosa lung infection (36). Others have used Bordetella pertussis (58) and Haemophilus infruenzae (39,50) in similar studies of chronic pneumonia.…”
Section: Johansen Ct Almentioning
confidence: 99%
“…Woods et al investigated the ability of virulent and avirulent strains to survive and persist in a rat model for respiratory infection with B. pertussis (64). Avirulent B. pertussis was not recovered after 3 days from lungs of infected rats, while virulent B. pertussis was recovered on days 3 and 7 after inoculation but not on days 10 and 14. Recovery of viable B. pertussis from lungs of infected rats was again possible on day 21.…”
mentioning
confidence: 99%
“…Electron micrographs of lungs of infected animals revealed that the lung cells contained B. pertussis which appeared viable at 14 days. The authors propose that B. pertussis was not recoverable on days 10 and 14 because the microbe was residing intracellularly inside lung cells, perhaps alveolar macrophage (64).…”
mentioning
confidence: 99%
“…Great apes hold the best promise for a realistic model of disease but are prohibitively expensive for all but the most focused of studies. Rabbits become infected but do not become ill. New studies using rats appear to be promising (40), but much investigation remains to be done toward characterization of this disease model.…”
mentioning
confidence: 99%